Numerical Investigation of Optical Properties in Carbon Tetrachloride-Filled Photonic Crystal Fibers - Thuy, Nguyen Thi; Thi Oanh, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 39 No 4DO - 10.25073/2588-1124/vnumap.4850, 2023)
In this work, we design circular lattice photonic crystal fibers using Lumerical Mode Solution software, its hollow core filled with carbon tetrachloride. Optical properties including effective refractive index, chromatic dispersion, nonlinearity, and fiber loss were investigated numerically in detail based on solving Maxwell's wave equations. The small effective mode areas of only a few µm 2 , and confinement loss as low as 14.799 dB/m at specific pump wavelengths were obtained. It was found that near-zero ultra-flattened chromatic dispersion with fluctuations of ±0.44 ps/nm.km spans from 1300 to 1830 nm. Three photonic crystal fibers with optimal structure and features were suggested for broadband supercontinuum generation orientation.